(untitled) (Journal of Energy and Safety Technology (JEST), 2023)
Traditional grid has been extensively studied for system security. For freestanding renewable energy-based minigrid, a three-source stand-alone minigrid is in this study examined for system security under large disturbances. By real-time simulation, rotor responses of the generators and voltage characteristics of the buses are assessed at sudden load change and under fault condition. Post-perturbation behaviour of the system shows synchronism is not compromised by any of the generators and the bus voltage profiles remains within their pre-perturbation statutory limits. This implies that a number of rotating machine-based energy mini-sources could be interconnected into a freestanding minigrid without compromising the stability of the system. The assessment could find use in predictive and corrective compensation for stability issues in mini integrated power systems and serve as simple generic investigative approach that could be integrated into Minigrids Remedial Action Scheme or Minigrids Energy Management System for dynamic security assessment of multi-machine island minigrids.